ESTIMATIONS OF CARBON STORAGE AND ECONOMIC VALUE OF MANGROVE FOREST ON THE NORTH COAST OF CAWAN ISLAND, INDRAGIRI HILIR - Emrinelson, Tri; Warningsih, Trisla (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2024)
Mangrove forests are important for human life and the surrounding environment, one of which is as a CO2 absorber and carbon storage. The North Coast of Cawan Island in Indragiri Hilir has a relatively good mangrove forest that is estimated to absorb and store more carbon. This study aims to (1) estimate the value of carbon storage in stands (stems), below-ground carbon (roots), litter, and sediment of mangrove forests, (2) estimate the CO2 absorption capacity of mangrove forests, and (3) estimate the economic value of absorption CO2 by mangrove forest on the North Coast of Cawan Island. The station determination method uses purposive sampling of five stations, each consisting of a transect with three plots measuring 10x10 m2. Measurement of stem and root biomass using the allometric method. Litter biomass measurement used the dry weight weighing method, and sediment carbon measurement used the Loss on Ignition (LOI) method. The result showed that average carbon storage in stems was 34.56 tons/ha, roots were 16.41 tons/ha, litter was 0.10 tons/ha, and sediment was 32.91 tons/ha. The estimated ability of mangrove forests to absorb CO2 is an average of 187.10 tons/ha or 636,450.59 tonnes for the entire North Coast of Cawan Island. The estimated economic value of mangrove forest carbon is an average of IDR 149,809,099 /ha or IDR 509,599,619,024 for the entire North Coast of Cawan Island.